2014
DOI: 10.1115/1.4027412
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Measuring Pull-off Stress of Wound-Treatment Polymers

Abstract: Skin wounds and burns compromise the body's natural barrier to bacteria and other pathogens. While many forms of wound dressings are available, polymeric films are advantageous for various reasons, ranging from the ease of application to durability. One common drawback of using polymeric films for a wound bandage is that the films tend to adhere to common inanimate objects. Patients spend hours in contact with soft and hard materials pressed against their skin, which, if the skin was dressed with a polymeric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Testing methods such as the ASTM 903, 106 which is a standard test method for peel or stripping strength of adhesive bonds, are used in the absence of specific peeling tests for wound dressings. A particular challenge in this regard is to standardise a material substrate to represent the skin in such testing, although a range of options potentially exists, such as elastomers (silicones), ethylene/methyl acrylate films, epoxy resins, textiles and metals, or alternatively, excised porcine skin 86,107,108 . Preliminary research towards the standardisation of testing of adhesive bandage tapes, which are, of course, much less complex than advanced foam‐based wound dressings, already indicated that the peeling forces depend on the width of the tape and storage conditions, two example properties that are typically not considered in the evaluation of adhesiveness of wound dressings 109 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing methods such as the ASTM 903, 106 which is a standard test method for peel or stripping strength of adhesive bonds, are used in the absence of specific peeling tests for wound dressings. A particular challenge in this regard is to standardise a material substrate to represent the skin in such testing, although a range of options potentially exists, such as elastomers (silicones), ethylene/methyl acrylate films, epoxy resins, textiles and metals, or alternatively, excised porcine skin 86,107,108 . Preliminary research towards the standardisation of testing of adhesive bandage tapes, which are, of course, much less complex than advanced foam‐based wound dressings, already indicated that the peeling forces depend on the width of the tape and storage conditions, two example properties that are typically not considered in the evaluation of adhesiveness of wound dressings 109 .…”
Section: Discussionmentioning
confidence: 99%
“…A particular challenge in this regard is to standardise a material substrate to represent the skin in such testing, although a range of options potentially exists, such as elastomers (silicones), ethylene/methyl acrylate films, epoxy resins, textiles and metals, or alternatively, excised porcine skin. 86 , 107 , 108 Preliminary research towards the standardisation of testing of adhesive bandage tapes, which are, of course, much less complex than advanced foam‐based wound dressings, already indicated that the peeling forces depend on the width of the tape and storage conditions, two example properties that are typically not considered in the evaluation of adhesiveness of wound dressings. 109 Importantly, theoretical and computational analyses such as those reported here can be used to identify influential factors, for example, as in Equations ( A9 and A10 ) (Appendix A.2 ), which point to the role of the dressing width in the skin loading state during removals, but details of theoretical‐computational frameworks for wound dressings are also lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%